1983
DOI: 10.1128/iai.39.3.1252-1259.1983
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between cecal population levels of indigenous bacteria and translocation to the mesenteric lymph nodes

Abstract: Translocation is defined as the passage of viable bacteria from the gastrointestinal tract to the mesenteric lymph nodes (MLN) and other organs. The extent of translocation of certain indigenous, oxygen-tolerant bacteria from the cecum to the MLN, spleen, liver, kidney, and peritoneal cavity were determined in diassociated or triassociated gnotobiotic mice. Minimal bacterial translocation occurred to the spleen, liver, kidney, or peritoneal cavity. However, most bacterial strains readily translocated to the ML… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
42
1
1

Year Published

1986
1986
2002
2002

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 168 publications
(46 citation statements)
references
References 22 publications
2
42
1
1
Order By: Relevance
“…21) Bacterial translocation can occur in situations where the number of bacteria exceeds a particular threshold. 22,23) Some mechanisms that enable them to do so are endocytosis by enterocytes, intracellular diffusion, non-specific uptake when there is intestinal damage, or transportation through M cells. Claassen et al 24) proved that LAB could adhere to and be taken up by M cells of the Peyer's patches and thus could be transported to underlying lymphoid follicles where they are subjected to immunological scrutiny by immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…21) Bacterial translocation can occur in situations where the number of bacteria exceeds a particular threshold. 22,23) Some mechanisms that enable them to do so are endocytosis by enterocytes, intracellular diffusion, non-specific uptake when there is intestinal damage, or transportation through M cells. Claassen et al 24) proved that LAB could adhere to and be taken up by M cells of the Peyer's patches and thus could be transported to underlying lymphoid follicles where they are subjected to immunological scrutiny by immune cells.…”
Section: Discussionmentioning
confidence: 99%
“…The major mechanisms postulated to promote BT are deficiencies in local host immune defenses, increased permeability of the intestinal mucosal barrier, and IBO. 24 A direct relationship between the increase in gram-negative bacterial population in the cecum and the magnitude of BT has been shown, 14 suggesting that bacterial overpopulation of the bowel is one of the major mechanisms that promotes BT in experimental models. In fact, Guarner et al 20 have shown recently that intestinal aerobic bacterial count in cecal stool is significantly increased in CCl 4 cirrhotic rats with BT as compared to cirrhotic rats without BT and normal rats.…”
Section: Discussionmentioning
confidence: 99%
“…In recent years, bacterial translocation (BT), defined as the passage of viable bacteria from the gastrointestinal tract to the mesenteric lymph nodes (MLNs), has been postulated to be an important step in the pathogenesis of enteric-origin bacterial infections in cirrhosis. [8][9][10][11][12][13] It is well known that BT is facilitated by the presence of intestinal bacterial overgrowth (IBO), 14 which in turn is favored by disturbances in bowel motility. 15,16 Because both IBO and slow orocecal transit occur in cirrhotic patients, 17,18 it is conceivable that the administration of a prokinetic drug might decrease the incidence of IBO, and thus reduce the risk of BT in these patients, by normalizing the delayed small intestinal transit time.…”
mentioning
confidence: 99%
“…The gastrointestinal mucosa acts as a barrier against bacterial invasion although pathogens can gain access, usually through specific receptor-mediated mechanisms. In the healthy animal the indigenous intestinal flora does not usually cross the intestinal epithelial but if they succeed it is only in small numbers which are killed and eliminated [30,31]. During fermented milk consumption we found high faecal counts of Lal and bifidobacteria.…”
Section: Discussionmentioning
confidence: 99%